Polygenic Prediction of Weight and Obesity Trajectories from Birth to Adulthood - Khera, Amit V; Chaffin, Mark; Wade, Kaitlin H; Zahid, Sohail; Brancale, Joseph; Xia, Rui; Distefano, Marina; Senol-Cosar, Ozlem; Haas, Mary E; Bick, Alexander; Aragam, Krishna G; Lander, Eric S; et al. (Cell, 2019)
Severe obesity is a rapidly growing global health threat. Although often attributed to unhealthy lifestyle choices or environmental factors, obesity is known to be heritable and highly polygenic; the majority of inherited susceptibility is related to the cumulative effect of many common DNA variants. Here we derive and validate a new polygenic predictor comprised of 2.1 million common variants to quantify this susceptibility and test this predictor in more than 300,000 individuals ranging from middle age to birth. Among middle-aged adults, we observe a 13-kg gradient in weight and a 25-fold gradient in risk of severe obesity across polygenic score deciles. In a longitudinal birth cohort, we note minimal differences in birthweight across score deciles, but a significant gradient emerged in early childhood and reached 12 kg by 18 years of age. This new approach to quantify inherited susceptibility to obesity affords new opportunities for clinical prevention and mechanistic assessment.